Energy efficiency in data centers and clouds - Hurson, Ali; Sarbazi-Azad, Hamid (Academic Press is an imprint of Elsevier, 2016)
Advances in Computers carries on a tradition of excellence, presenting detailed coverage of innovations in computer hardware, software, theory, design, and applications. The book provides contributors with a medium in which they can explore their subjects in greater depth and breadth than journal articles typically allow. The articles included in this book will become standard references, with lasting value in this rapidly expanding field.
Keywords: Data centers -- Energy consumption.; elektronické knihy; electronic books